Extended Inflammation Parameters (EIP) as Markers of Inflammation in Systemic Sclerosis - Anna Kowalska-Kępczyńska; Mateusz Mleczko; Kamila Komajda; Małgorzata Michalska-Jakubus; Dorota Krasowska; Maciej Korpysz (Hindawi Limited, 2024)
Background. Systemic sclerosis (SSc) is an autoimmune disease characterized by inflammation, progressive vasculopathy, and fibrosis of skin and internal organs. The aim of the study was to evaluate extended inflammatory parameters (EIP) in patients with SSc in comparison to the control group of healthy subjects. Methods. A total of 28 patients with SSc and 29 healthy controls (HCs) were included in the study. The following EIP parameters were analyzed: neutrophil reactive intensity (NEUT-RI), neutrophil granularity intensity (NEUT-GI), antibody-synthesizing lymphocytes (AS-LYMP), and reactive lymphocytes (RE-LYMP). Results. Patients with SSc showed significantly higher values of parameters determining neutrophil reactivity and neutrophil granularity when compared to HCs (respectively, 49.16 FI vs. 44.33 FI, p<0.001, and 152.01 SI vs. 147.51 SI, p<0.001). Moreover, patients with SSc had higher absolute numbers of RE-LYMP than HCs (0.69 × 103/µl vs. 0.04 × 103/µl, p<0.001). Importantly, significant correlations between the RE-LYMP and either IL-6 (R = 0.447, p<0.001) or ESR (R = 0.532, p<0.001) were found among patients with SSc. Conclusions. Changes in NEUT-RI, NEUT-GI, and RE-LYMP levels positively correlate with inflammation in SSc and, thus, could potentially be used as an additional reliable inflammatory biomarker to assess inflammation in this disease.